Evaluation of Aloe vera leaf gel as a Natural Flocculant: Phytochemical Screening and Turbidity removal Trials of water by Coagulation flocculation - AGBANGNAN DOSSA, COKOU PASCAL (My University, 2016)
This study focused on the evaluation as natural flocculant in water clarification and identification of major phytochemical groups of Aloe vera, a plant which belongs to Liliaceae family. Phytochemical groups such tannins, saponins, mucilage, flavonoids, anthracene derivatives, quinone derivatives and proteins were identified. However, they were devoid of alkaloids, reducing compounds, cardiotonic glycosides in this plant. The results obtained for determined Aloe vera constituent materials showed a high rate of organic matter in this plant (81.05% of dry matter) and low levels of dry matter and ash (respectively 4.2% of fresh matter and 12.04% of dry matter). The clarification tests using this plant for very turbid surface water (turbidity: 185-200 NTU, Suspended solids: 160-170, Obvious color: 275-285 Pt Co), showed a good elimination of turbidity and suspended solids. Removal efficiency was 72% for turbidity, 91% for suspended solids and 15% for the obvious color. Aloe vera can be promoted as a good natural floculant in surface water clarification.
Keywords: Phytochemical Screening; Aloe vera; natural flocculant; turbidity; suspended solids; ash content